"Temper Discipline with Kindness": Female Officers at the Old Melbourne Gaol and City Watch House, 1845–1935. (1st November 2022) - Viney, Hannah
Abstract : As ideas of penal reform and the rise of the Woman Movement permeated Victorian society in the decades spanning the turn of the twentieth century, the duties of female penal employees changed. From the opening of the Old Melbourne Gaol in 1845 female warders and matrons were an integral part of the Victorian penal system, responsible for overseeing the incarceration of convicted women. Their work paralleled that of their male counterparts. Demands by women's organisations to increase and extend women's employment opportunities also impacted on the nature of their work. By the time the Melbourne City Watch House opened in 1909, women were expected to reform the charges in their care, not only to ensure convicted women's safety in the prison but also to enable the rehabilitation of "fallen" women into respectability. This article analyses the evidence of women's prison labour and traces the changing expectations of women's labour in the penal system.